2019
DOI: 10.1101/659789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host carbon dioxide concentration is an independent stress for Cryptococcus neoformans that affects virulence and antifungal susceptibility

Abstract: The ability of Cryptococcus neoformans to cause disease in humans varies significantly among strains with highly related genotypes. In general, environmental isolates of pathogenic species such as C. neoformans var. grubii have reduced virulence relative to clinical isolates, despite having no differences in the expression of the canonical virulence traits (high temperature growth, melanization and capsule formation). In this observation, we report that environmental isolates of C. neoformans tolerate host CO2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is also interesting that host levels of carbon dioxide further exacerbate the fitness defect of acl1 Δ on host-like media. Our group has recently shown that host concentrations of carbon dioxide is an independent stress with relevance to virulence (8). Specifically, environmental strains with low mammalian virulence do not tolerate host concentrations of carbon dioxide while clinical strains do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting that host levels of carbon dioxide further exacerbate the fitness defect of acl1 Δ on host-like media. Our group has recently shown that host concentrations of carbon dioxide is an independent stress with relevance to virulence (8). Specifically, environmental strains with low mammalian virulence do not tolerate host concentrations of carbon dioxide while clinical strains do.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is now well-recognized that additional infection-related traits remain to be discovered and characterized (7). Recently, we and others have become interested in the hypothesis that a deeper understanding of this variation may emerge by exploring the traits and processes required for C. neoformans to transition from an environmental niche to the host (8).…”
Section: Introductionmentioning
confidence: 99%